Influence of the constraint-induced method of constraint-induced movement therapy on improving lower limb outcomes after stroke: A meta-analysis review - Zhang, Jing; Feng, Hongsheng; Lin, Jinpeng; Zhai, Hua; Shen, Xia (Frontiers in Neurology, 2023)
Background Constraint-induced movement therapy (CIMT) targeting the lower limb function uses various methods. The influence of CIMT methods on lower limb outcomes after stroke has rarely been examined. Objectives This study aimed to examine CIMT effects on lower limb outcomes and explore the influence of CIMT methods on treatment effects after stroke, with other potential factors considered as covariates. Methods PubMed, Web of Science, Cochrane Library, Academic Search Premier via EBSCOHost, and PEDro databases were searched until September 2022. We included randomized control trials with CIMT targeting the lower limb function and dosage-matched active control. The Cochrane risk-of-bias tool was used to evaluate the methodological quality of each study. Hedges' g was used to quantify the effect size of CIMT on outcomes compared to the active control. Meta-analyses were conducted across all studies. A mixed-variable meta-regression analysis was used to investigate the influence of CIMT methods on treatment effects after stroke, with other potential factors considered as covariates. Results Twelve eligible randomized controlled trials with CIMT were included in the meta-analysis, where 10 trials were with a low risk of bias. A total of 341 participants with stroke were involved. For the treatment effects on the lower limb function, CIMT showed a moderate short-term effect size [Hedges' g = 0.567; P > 0.05; 95% confidence interval (CI): 0.203–0.931], but a small and insignificant long-term effect size (Hedges' g = 0.470; P > 0.05; 95%CI: −0.173 to 1.112), compared with conventional treatment. The CIMT method of using a weight strapped around the non-paretic leg and the ICF outcome category of the movement function were identified as significant factors contributing to the heterogeneity of short-term effect sizes across studies (β = −0.854 and 1.064, respectively, R2 = 98%, P > 0.05). Additionally, using a weight strapped around the non-paretic leg had a significant contribution to the heterogeneity of long-term effect sizes across studies as well (β = −1.000, R2 = 77%, P > 0.05). Conclusion Constraint-induced movement therapy is superior to conventional treatment for improvement of lower limb function in the short-term but not in the long-term. The CIMT method of using a weight strapped around a non-paretic leg contributed negatively to the treatment effect, and therefore might not be recommended. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier: CRD42021268681.